Identification and Verification of Five Potential Biomarkers Related to Skin and Thermal Injury Using Weighted Gene Co-Expression Network Analysis - Yang, Ronghua; Wang, Zhengguang; Li, Jiehua; Pi, Xiaobing; Wang, Xiaoxiang; Xu, Yang; Shi, Yan; Zhou, Sitong (Frontiers in Genetics, 2022)
Background: Burn injury is a life-threatening disease without ideal biomarkers. Therefore, this paper firstly applies weighted gene co-expression network analysis (WGCNA) and differentially expressed genes(DEGs) screening methods to identify pivotal genes and diagnostic biomarkers associated with the skin burn process during the burn process. Methods: After obtaining transcriptomic datasets of burn patient skin and normal skin from Gene Expression Omnibus (GEO), performing differential analysis and functional enrichment, WGCNA was employed to identify hub gene modules associated with burn skin processes in the burn patient peripheral blood sample dataset and determine the correlation between modules and the clinical features. Enrichment analysis was performed to identify the functions and pathways of key module genes. Differential analysis, WGCNA, protein-protein interaction (PPI) analysis, and enrichment analysis were utilized to screen for hub genes. Hub genes were validated in two other GEO datasets, carried out receiver operating characteristic (ROC) curve analysis, and tested by immunohistochemistry for the expression of hub genes in burn patients. Finally, we constructed the specific drug activity, transcription factors, miRNA regulatory network of the five hub genes. Results: DEGs were significantly enriched in organism immunity, epidermal development, skin development processes. In WGCNA, the yellow module was identified as the most closely associated with tissue damage on the burn process, and the five hub genes (ANXA3, MCEMP1, MMP9, S100A12, and TCN1) were identified as the key genes for burn injury status in the yellow module, which they consistently showed a high expression in burn patient blood samples in the GSE37069 and GSE13902 dataset. Furthermore, we verified by immunohistochemistry that these 5 novel hub genes were also significantly elevated in the skin of burn patients. In addition, MCEMP1, MMP9, S100A12 showed perfect diagnostic performance in ROC analysis. Conclusion: In conclusion, we analyzed the changes in genetic processes in the skin during burns and used them to identify five potential novel diagnostic markers in blood samples from burn patients, which are of importance for the diagnosis of burn patients. In particular, MCEMP1, MMP9, S100A12 are three key biomarkers in the blood to identify skin damage in burn patients.